Inhibition of Escherichia coli and Bacillus subtilis FtsZ Polymerization and Bacillus subtilis Growth by Dihydroxynaphtyl Aryl Ketones - Araya, Gissela; Benites, Julio; Reyes, Juan S.; Marcoleta, Andrés E.; Valderrama, Jaime A.; Lagos, Rosalba; Monasterio, Octavio (Frontiers in Microbiology, 2019)
The increasing detection of virulent and/or multidrug resistant bacterial strains makes necessary the development of new antimicrobial agents acting through novel mechanisms and cellular targets. A good choice are molecules aimed to interfere with the cell division machinery or divisome, which is indispensable for bacterial survival and propagation. A key component of this machinery and thus a good target is FtsZ, a highly conserved GTPase protein that polymerizes in the middle of the cell on the inner face of the cytoplasmic membrane forming the Z ring, which acts as a scaffold for the recruitment of the divisome proteins at the division site. In this work, we tested the inhibitory effect of five diaryl naphtyl ketones (dNAK) molecules on the in vitro polymerization of both Escherichia coli and Bacillus subtilis FtsZ (EcFtsZ and BsFtsZ, respectively). Among these compounds, dNAK 4 showed the strongest inhibition of FtsZ polymerization in vitro, with an IC50 of 2.3 ± 0.06 μM for EcFtsZ and 9.13 ± 0.66 μM for BsFtsZ. We found that dNAK 4 binds to GDP-FtsZ polymers but not to the monomer in GTP or GDP state. This led to the polymerization of short and curved filaments, rings, open rings forming clusters, and in the case of BsFtsZ, a novel cylindrical structure of stacked open rings. In vivo, dNAK 4 had almost no effect on the growth of E. coli in liquid culture, in contrast to the strong inhibitory effect observed over B. subtilis growth. The insensitivity of E. coli to this compound is probably related to the impermeability of dNAK 4 to the outer membrane. The low amount of this compound required to inhibit several of the bacterial strains tested and the lack of a cytotoxic effect at the concentrations used, makes dNAK 4 a very good candidate as a starting molecule for the development of a new antibiotic